SELECTED UNDERTAKINGS OF SHARING TRANSPORT SERVICES BY CONTEMPORARY CONSUMERS: RESEARCH RESULTS - Beata Tarczydło; Anna Kondak; Adrian Konior (Polityki Europejskie, Finanse i Marketing, 2020)
The primary objective of the paper is to discuss examples of sharing transport services in the Polish market as manifestations of the application of the idea of the sharing economy by contemporary consumers. Based on the essence of the considered concept and/or economy model, a review of previous studies was made and subjects for the authors’ own research were selected. The case study and online survey methods were used. In particular, services offered under the Traficar, Uber, and Wavelo brands were analysed. The research that was conducted made it possible to identify the determinants, as well as the advantages and disadvantages, of this type of market practice. It also allowed to develop certain recommendations for marketers interested in the methodical application of sharing services and/or products.